Identifying Productivity and Amenity Effects in Interurban Wage Differentials - Beeson, Patricia E.; Eberts, Randall W. (The Review of Economics and Statistics, 1989)
The relative importance of amenity and productivity differences in explaining wage differentials across metropolitan areas is estimated by utilizing the land and labor market clearing conditions for locational equilibrium of household and firms. Estimates of equilibrium wages and rents, along with estimates of households' budget shares and national income to land and labor rations, are used to identify amenity and productivity components of wages for each metropolitan area in the sample. While both components are found to be important, the productivity component, on average, accounts for a larger share of the intermetropolitan wage differentials. Copyright 1989 by MIT Press.